1991
DOI: 10.3171/jns.1991.75.3.0402
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of chronic pain by epidural spinal cord stimulation: a 10-year experience

Abstract: Epidural spinal cord stimulation by means of chronically implanted electrodes was carried out on 121 patients with pain of varied benign organic etiology. In 116 patients, the pain was confined to the back and lower extremities and, of these, 56 exhibited the failed-back syndrome. Most patients were referred by a pain management service because of failure of conventional pain treatment modalities. Electrodes were implanted at varying sites, dictated by the location of pain. A total of 140 epidural implants wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
113
3
4

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(122 citation statements)
references
References 23 publications
2
113
3
4
Order By: Relevance
“…Kumar, 33 Richardson 34 and Cole et al 37 could not demonstrate good e ects, although results of Richardson's study are possibly distorted by the fact that only one patient out of 10 had paresthesia in the pain region, which is, as formerly mentioned, essential for good results. Barolat 35 found pain due to spinal cord injury by far the worst responder of the chronic pain syndromes he had studied.…”
Section: Clinical Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Kumar, 33 Richardson 34 and Cole et al 37 could not demonstrate good e ects, although results of Richardson's study are possibly distorted by the fact that only one patient out of 10 had paresthesia in the pain region, which is, as formerly mentioned, essential for good results. Barolat 35 found pain due to spinal cord injury by far the worst responder of the chronic pain syndromes he had studied.…”
Section: Clinical Resultsmentioning
confidence: 89%
“…The possible advantage of extended trial periods should however been weighted against the higher infection rate associated with percutaneous trials. 22 When patients are considered to be candidates for SCS therapy, there must be an objective basis for the pain complaints, 33,69 and, as mentioned before, the integrity of the ®bres to be stimulated must be guaranteed.…”
Section: Ischemic Painmentioning
confidence: 99%
“…Epidural spinal cord stimulation has long been used to treat intractable pain in patients (29,111,116,145,146,149,177,183,188,227,230). Sayenko et al (220) showed that lumbosacral epidural stimulation activated widespread rostral and caudal areas of the lumbar spinal cord, involving afferent and efferent pathways, in a patient with chronic SCI.…”
Section: Epidural Spinal Cord Stimulationmentioning
confidence: 99%
“…The positioning of the spinal electrode should be precise in order to allow for overlap of the pain area during trial stimulation. This fact has been shown to be important for long-term efficacy of spinal cord stimulation (SCS) 24,25 . The SCS appears to be most effective in patients with impartial and postcordotomy pain 5 .…”
Section: Therapeutic Optionsmentioning
confidence: 99%